The role of adolescent pregnancy on the new meaning of sexuality - Sandra Castrillón C (Universidad de Antioquia, 2010)
This article presents the findings of the research accomplished in the master in psychoanalytic research for the Department of Psychoanalysis in the University of Antioquia in 2008. Objetive: to respond to the question about the function that a child has for a teenager woman in the process of resignifying infantile sexuality. Methodology: seven adolescent women with ages ranging from 15 to 17 years were interviewed, five girls were pregnant and two were already mothers. Results: teenagers became pregnant from her desire, not because of ignorance about contraceptive methods or factors external to them. Through pregnancy and the subsequent presence of the child, symbolic issues are handled to be resolved in adolescence: the duel for the parental objects, the body of the child and the child role. Conclusions: pregnancy in the adolescence allows the young woman to resignify the infantile sexuality, where the oldest objects of the subject are included: the parental objects. Discussion: these findings become innovative because in this research an explanation is offered from the point of view of the choice of the subject, in terms of his subjective responsibility